Fundamental motor skills: A systematic review of terminology. Issue 7 (3rd April 2018) - Logan, Samuel W.; Ross, Samantha M.; Chee, Keanu; Stodden, David F.; Robinson, Leah E.
ABSTRACT: The three aims of this systematic review are to describe: (1) use of the term fundamental motor/movement skills (FMS) in published articles; (2) the quality of definitions; and (3) relative use of process- and product- oriented assessments to measure FMS. The inclusion criteria included: (a) peer-reviewed article, (b) printed in English, (c) published between January 2000 and 31 December 2015, (d) presence of either the term "fundamental motor or movement skill" in the title and/or abstract, and (e) FMS were a measured outcome. There has been an increase in the number of publications on FMS in recent years, with the majority of studies conducted in Australia ( n  = 41, 33%). Approximately 24% of studies ( n  = 30) did not provide any explicit definition of FMS. A majority of studies reported the use of process-oriented measures ( n  = 98, 79%) compared to product-oriented measures ( n  = 23, 19%), and few studies used both ( n  = 6, 5%). We recommend that researchers provide: (1) an operational definition of FMS that states FMS are the "building blocks" (or similar terminology) of more advanced, complex movements; (2) specific categories of skills that compose FMS; and (3) at least one specific example of a FMS.